Integrated Farming System: Prospects in Bangladesh - Al Mamun, Shamim; Nasrat, Fouzia; Debi, Momota Rani (Journal of Environmental Science and Natural Resources, 2012)
Farmers of Bangladesh generally practice subsistence farming where they need to produce a continuous, reliable and balanced supply of foods, as well as cash for basic needs and recurrent farm expenditure. Therefore, there is a need to develop suitable integrated farming systems for such farmers since single crop production enterprises are subject to a high degree of risk and uncertainty because of seasonal, irregular and uncertain income and employment to the farmers. Integrated Farming System (IFS) can eradicate all these constraints by not only solving most of the existing economic and even ecological problems, but also provide other household needs like fuel, fertilizer and feed, besides increasing productivity of the farm manifold. DOI: http://dx.doi.org/10.3329/jesnr.v4i2.10161 J. Environ. Sci. & Natural Resources, 4(2): 127-136, 2011